PALEOSCENE 16. Sequence Stratigraphy and Chronostratigraphy: Problems of Definition and Precision in Correlation, and Their Implications for Global Eustasy - Miall, Andrew (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1994)
Abstract Sequence stratigraphy, as proposed by the Exxon school, represents a new paradigm in geology, whereby sequences are regarded as eustatic in origin, and are therefore to be considered superior, as chrono stratigraphic indicators, to all other recorders of stratigraphie age. Such an approach is built on circular reasoning and may result in a sequence framework consisting of a poorly correlated assortment of regional events with little or no global significance. Sequence correlation beyond the physical tracing that can be accomplished within an individual basin depends on the use of conventional chronostratigraphic indicators, primarily biostratigraphy. Biostratigraphic correlation is characterized by imprécisions reflecting therates of evolution and fossil preservation. Global correlation and dating of biozones is hampered by faunal/floral provincialism and errors inherent in numerical (e.g., radiometric) dating. At present, the best available chronostratigraphic dating methods contain potential errors of up to a few million years.This is equal to or greater than the event spacing of the "third-order cycles",which constitute the main subdivisions of Exxon's global cycle chart. Therefore, sequence frameworks in different basins capnot be reliably distinguished on the basis of chronostratigraphic evidence. Much research indicates the importance of regional tectonic processes in the generation of stratigraphie se-quences. For this reason, the test ofglobal synchroneity remains central to a resolution of the tectonic-versus-eu-static debate for these cycles, and this currently constitutes one of the most vigorous and exciting areas of stratigraphic research.